Harmonic Behaviour of RGB WLED - Dogansahin, Kadir; Ayaz, Ramazan; Bozkurt, Altug; Kekezoglu, Bedri (IEEE, 2019)
For the last few years, there has been a decrease in electricity consumption for lighting purposes. The reason for this decrease is the widespread use of energy saving lighting elements that have high efficacy factor. LEDs are one of these lighting elements and have a very important role on energy saving lighting. On the other hand, power quality problems have started to be experienced more frequently and seriously, so it has become an important issue nowadays. Light emitting diodes are a closely related in both subjects. In this study, the harmonic behavior of RGB WLEDs, which has gained importance recently and has become increasingly widespread, has been investigated. RGB WLEDs, which are quite different from monochrome LEDs in terms of package contents and driver circuit, are expected to behave differently in terms of harmonics. In order to observe that, an appropriate test setup has been established and the power quality measurements of an RBG WLED sample have been performed for different operating cases. In the conclusion of the study, the enlightening results about the harmonic behavior of RGB WLEDs were obtained.
Keywords: Distortion measurement; Light emitting diodes; Power conversion harmonics; RGB WLED; Relative spectral power; GREEN; RED; Energy & Fuels; Engineering